Revolutionizing Mosquito Control: A Nobel Approach with Cow Dung-Based Herbal Repellents - Roy, Aparup (International Journal of Scientific Research in Biological Sciences, 2024)
Mosquito-borne diseases pose significant health threats worldwide, emphasizing the urgent need for effective and affordable mosquito repellents. This study investigates the development and efficacy of a novel mosquito repellent derived from cow dung supplemented with herbal ingredients. The primary objective was to assess the feasibility and effectiveness of utilizing cow dung as a base for mosquito repellent formulation, comparing its efficacy with commercially available alternatives. Through a series of experiments and comparative analyses, it was determined that the cow dung-based mosquito repellent exhibited a remarkable effectiveness, surpassing commercial repellents by 20%. The formulation process was meticulously examined, detailing the incorporation of herbal ingredients to enhance repellent properties. Moreover, the study sheds light on the potential health and environmental implications associated with the use of conventional mosquito repellents containing synthetic pyrethroids and DDT, emphasizing the need for safer alternatives. The herbal mosquito repellent developed in this study offers a cost-effective, eco-friendly solution with minimal health risks, thereby advocating for its adoption as a viable alternative to commercial repellents. Furthermore, this research underscores the importance of industry adoption to facilitate the widespread availability and utilization of herbal mosquito repellents, thereby mitigating health risks associated with conventional alternatives. Overall, this study contributes to the growing body of knowledge on sustainable vector control methods and highlights the potential of natural remedies in combating mosquito-borne diseases.